Does the Proximity of the Area Affect in Incidence of Stunting? : Study on Densely Populated Provinces in Indonesia - Astridya Paramita; Nailul Izza; DwiHapsari Tjandrarini; Agung Dwi Laksono (Institute of Medico-legal Publications Pvt Ltd, 2022)
The prevalence of stunting in Indonesia is still above WHO standards, so it needs to be addressed immediately,given the adverse effects on individuals and countries. This study aims to analyze the incidence of stunting inEast Java by paying attention to the proximity of the area as an effort to solved stunting problems. The studywas conducted using secondary data from 2017 from official government agency reports. Administrative area(regency/city) analysis unit. Analysis using spatial regression test. The results show that Moran’s I test showsa spatial dependency or location autocorrelation (p <0.20). The Lagrange Multiplier SAR spatial regression testcan explain that spatial factors can increase 5% greater (75%) of the 5 selected factors that cause toddler stunting,compared to using the OLS classic regression test. It could be concluded that spatial factors, namely geographicareas, can increase the percentage of clarity in the regression modeling for the incidence of stunting in an area. Inthis study, spatial factors are known to be associated with regional proximity and ethnic similarity, namely theMadurese ethnicity.